Dampak Sektor Pertanian, Perikanan Dan Pariwisata Terhadap Pertumbuhan Ekonomi - Hendricus Lembang; Semuel Batlajery (Universitas Musamus,Merauke,Papua, 2021)
The economic growth of Merauke Regency relies on strategic sectors that can spur development for the welfare of society. The purpose of this study is to determine the effect of the agriculture, fishery and tourism sectors on the economic growth in Merauke Regency by using secondary data obtained from the Central Statistics Agency from 2012-2017. The data analysis technique uses regression quantitative analysis with the analysis tool of the AMOS (Analysis of Moment Structures). The results of the study show that the agriculture, fishery and tourism sectors have a positive and significant effect on the economic growth of Merauke Regency.